Menakar Lembaran Baru Penggunaan QRIS Pada Electronic Payment Gateways - Ida Ayu Adi Cintya Dewi Kemenuh; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
This research has a purpose to determine the management model of Tourism Attraction based on Sustainable Tourism Development. This study used qualitative methods, determining informants by purposive sampling with 7 informants. The data in this study were analyzed in several stages starting with data collection, data reduction, data presentation, and finally drawing conclusions and verification. The suggestion from this study is to provide guidance to the people of Beraban Village, traders in the Tanah Lot Tourist Attraction area, and all staff who work at the Tanah Lot Tourist Attraction so that they can be carried out more actively in developing this Tourist Attraction area. It is hoped that all people will take part in providing even better service in the future because there are a lot of tourism potentials in the Tanah Lot Tourist Attraction area if studied and explored more deeply.